Odpowiedź :
Odpowiedź:
[tex]3(4 + 2) - 10 = 3 \times 6 - 10 = 18 - 10 = 8 \\ 5(6 - 3) - 8 = 5 \times 3 - 8 = 15 - 8 = 7 \\ 7(21 - 18) - 8 = 7 \times3 + 2 = 21 +2 = 23 \\ 8(14 - 10) - 20 = 8 \times 4 - 20 = 32 - 20 = 12 \\ - 3(4 + 1) + 30 = - 3 \times 5 + 30 = - 15 + 30 = 15[/tex]
[tex] - 5(8 - 3) + 50 = - 5 \times 5 + 50 = - 25 + 50 = 25[/tex]
Odpowiedź:
a
3(4+2)-10= 3 * 6 - 10 = 18 - 10 = 8
b
5(6-3)-8= 5 * 3 - 8 = 15 - 8 = 7
c
7(21-18)+2= 7 * 3 + 2 = 21 + 2 = 23
d
8(14-10)-20= 8 * 4 - 20 = 32 - 20 = 12
e
-3(4+1)+30= -3 * 5 + 30 = -15 + 30 = 15
f
-5(8-3)+50= -5 * 5 + 50 = -25 + 50 = 25
Szczegółowe wyjaśnienie: